Seventh Five Year Plan (1985-90) Draft Annual Plan Proposal for 1989-90 Volume-I Introduction, Plan Review and Statements Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1985)
The Andaman and Nicobar Group of Islands comprises 572 islands (including 266 rocks) with a total geographical only area of 8249 Sq. KM. the major group of islands namely Andaman and Nicobar are separated from each other by a stretch of about 100 km of high sea Known as 10° Channel These Islands are rich in sea and forest wealth. the total population in these islands is 1,88,741 as per 1981 census, of which the work force is 62680. 16.39% of the Work Force are cultivators, 3.73% agricultural labourers, 2.91 engaged in household industry and 76.97% are other workers.
Andaman and Nicobar Administration